Kegiatan MBKM UNJ di Kampung Eduwisata Bhinneka: Kolaborasi Mahasiswa dan Komunitas dalam Pembuatan Media Promosi Wisata - Khrisnamurti, Khrisnamurti; Sidabutar, Raja; Ramadhan, Alfandi Wahyu; Afriansyah, Agung (Jurnal Pemberdayaan Pariwisata; Vol 7 No 1 (2025): Jurnal Pemberdayaan Pariwisata, 2025)
The main goal is to support the local community, especially the tourism awareness group (Pokdarwis), in using digital media to strengthen the image and attractiveness of Kampung Eduwisata Bhinneka. The activity used a descriptive qualitative approach with participatory observation. Students were directly involved in every step of the process, including identifying promotional needs, planning content with local managers, conducting content creation training, and publishing content on social media platforms. The results of this program include various promotional media such as a profile video, tourism package video, Instagram feeds, an official website, and a pocket book as a short guide for visitors. The active participation of local residents in the student-led training significantly improved their understanding of how to use graphic design and video editing tools. Social media analytics showed increased engagement, and feedback from the Pokdarwis group confirmed improved confidence in managing their own promotions. In conclusion, this activity highlights the importance of collaboration between educational institutions and local communities in developing community-based tourism. The structured and participatory training helped improve the community’s digital literacy. The recommendation is to continue digital training, use more diverse promotional platforms, and create more innovative content so that Kampung Eduwisata Bhinneka can compete effectively in today’s digital tourism landscape . Keywords:  promotional media, Merdeka Belajar Kampus Merdeka (MBKM). community based tourism (CBT